2017
DOI: 10.17226/24781
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management and the Opioid Epidemic

Abstract: Years of sustained, coordinated, and vigilant effort will be required to contain the present opioid epidemic and ameliorate its harmful effects on society. At least 2 million people have an opioid use disorder (OUD) involving prescription opioids, and almost 600,000 have an OUD associated with heroin (HHS, 2016). These numbers are likely to increase in the coming years, regardless of what policies are put in place. Follow-up studies of individuals receiving treatment for OUD involving heroin (e.g., Hser et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 123 publications
(157 reference statements)
0
28
0
4
Order By: Relevance
“…36,37 This is especially important since pharmacy students possess higher than average prevalence of risky substance use behaviors 38 and are an essential component of overdose prevention and response. 18,39 Surveys of practicing pharmacists have shown that despite successful programs on overdose education, 40 pharmacists continue to lack confidence and willingness to prescribe and dispense naloxone. 41,42 One way to easily integrate training with an active learning component is to pair naloxone training with basic life support training a requirement of nearly all health professional schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 This is especially important since pharmacy students possess higher than average prevalence of risky substance use behaviors 38 and are an essential component of overdose prevention and response. 18,39 Surveys of practicing pharmacists have shown that despite successful programs on overdose education, 40 pharmacists continue to lack confidence and willingness to prescribe and dispense naloxone. 41,42 One way to easily integrate training with an active learning component is to pair naloxone training with basic life support training a requirement of nearly all health professional schools.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, student pharmacists should be trained to identify these patients at risk and be able to provide naloxone education and training. 18 This study seeks to assess differences in the retention of knowledge (objective data) and impressions of overdose prevention efforts (subjective data) between student pharmacists who received the content delivered by a 50-minute lecture only and those who received the same lecture and completed an objective structured clinical examination (OSCE) of interactive counseling with standardized patient actors. Overdose education and naloxone training was recently implemented into the required curriculum of the College of Pharmacy at the University of Rhode Island in an effort to better prepare student pharmacists to identify intervention opportunities with at-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…The tragic example of the opioid epidemic shows industry’s harmful role in fuelling overuse through misleading marketing, biased medical education programmes, kickbacks, and manipulation of professional and patient organisations 12. These efforts transformed prescribing: opioids became drugs of choice for chronic non-cancer pain despite the lack of evidence of benefit.…”
Section: What Drives Overuse?mentioning
confidence: 99%
“…According to one, widely repeated account, the problem lies largely with pharmaceutical companies who have recklessly marketed opioids. Journalists and researchers tell and retell the story of Purdue Pharma's aggressive and highly successful marketing campaign to persuade physicians to prescribe Oxycontin to their chronic pain patients (e.g., Meier, 2018;Quinones, 2017;Zhang, 2017). In support of this explanation, American physicians were prescribing three times more opioids in 2012 than in 2001 (our calculations, see Results).…”
Section: Introductionmentioning
confidence: 99%